Bridging accessibility gaps in urban community-based basic older adult care: a comprehensive framework validated in Xi’an, China - Zhang, Yuyuan; Zhou, Ming; Hu, Jinrong; Wang, Ruoying (Frontiers in Public Health, 2025)
ObjectivesAccessibility is a critical factor in ensuring equitable public services. In urban older adult care systems, resource allocation and service disparities present unique challenges. The classical “5A” theory—availability, accessibility, affordability, adaptability, and acceptability—provides a robust framework for evaluating service delivery. However, its application in urban older adult care, especially in rapidly aging societies like China, remains limited. This study aims to develop and validate a framework to address affordability, resource allocation, and service mismatches in urban older adult care systems.MethodsA web-based cross-sectional study was performed in 2023. A multi-phase methodology was adopted to construct the framework, grounded in the “5A” theory. Indicators were refined through expert consultations using the Delphi method, involving 20 experts, while the entropy weight method ensured objective indicator weighting. The framework was empirically validated in Xi’an, China, using survey data collected from 438 older adult residents across urban strata. A fuzzy comprehensive evaluation (FCE) method was employed to assess accessibility and identify key service gaps.ResultsThis study constructs a comprehensive evaluation framework for basic older adult care services (BECS), structured around 5 primary dimensions, 14 sary indicators, and 37 tertiary indicators. Empirical validation in Xi’an further demonstrates the framework’s scientific rigor and practical applicability. While the framework identifies strong spatial accessibility (3.8815), it also reveals critical gaps in affordability (3.1347) and psychological care (3.0862), confirming its effectiveness in diagnosing systemic disparities and guiding policy interventions.ConclusionThis study introduces a novel accessibility evaluation framework tailored for basic older adult care services, addressing critical gaps in affordability, psychological care, and service responsiveness. Empirical results validate the framework’s practicality and its alignment with the real-world conditions of urban aging societies. Furthermore, an innovative “Matching-Realization-Satisfaction” improvement pathway is proposed, offering actionable strategies to enhance accessibility and optimize service delivery. This framework serves as a replicable model for advancing equitable older adult care in rapidly aging urban communities.